2009
DOI: 10.1177/0265659009102984
|View full text |Cite
|
Sign up to set email alerts
|

Speech and language therapists and teachers working together: Exploring the issues

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 15 publications
3
51
0
4
Order By: Relevance
“…In the case of the consultancy approach (McCartney et al, 2011), mainstream staff failed to implement the amount of language-learning activity required to adhere to the therapeutic program possibly because the staff simply did not have sufficient resources to manage the added demands of providing the intervention program. Indeed, there is evidence that SLP consultation may not necessarily lead to changed teacher behaviour (Noell & Witt, 1999), that teachers may not report benefiting from SLP consultations (Dockrell & Lindsay, 2001), and may have little access to SLPs for consultation (Baxter, Brookes, Bianchi, Rashid, & Hay, 2009). The bottom line is SLP-educator collaboration will be ineffectual (or nonexistent) if the partners lack the necessary time or other resources to implement services appropriately.…”
Section: The Challenge Of Changementioning
confidence: 99%
“…In the case of the consultancy approach (McCartney et al, 2011), mainstream staff failed to implement the amount of language-learning activity required to adhere to the therapeutic program possibly because the staff simply did not have sufficient resources to manage the added demands of providing the intervention program. Indeed, there is evidence that SLP consultation may not necessarily lead to changed teacher behaviour (Noell & Witt, 1999), that teachers may not report benefiting from SLP consultations (Dockrell & Lindsay, 2001), and may have little access to SLPs for consultation (Baxter, Brookes, Bianchi, Rashid, & Hay, 2009). The bottom line is SLP-educator collaboration will be ineffectual (or nonexistent) if the partners lack the necessary time or other resources to implement services appropriately.…”
Section: The Challenge Of Changementioning
confidence: 99%
“…Utilizar escalas de observación de las dificultades lingüísticas en el aula, con buenas propiedades psicométricas y que no requieran mucho tiempo para completarlas, facilitaría el trabajo tanto del colectivo docente como de los profesionales que realizarán posteriormente la evaluación formal del niño. Los beneficios del trabajo conjunto con los docentes conllevarían una mejora en las habilidades de comunicación del niño y una mayor autoestima (Baxter, Brookes, Bianchi, Rashid, & Hay, 2009). Por tanto, resulta relevante el asesoramiento a dicho colectivo para una detección eficaz de las posibles dificultades que puedan existir en el aula, y que a veces pasan desapercibidas en el entorno más cercano al niño, ya que como se ha comentado, las dificultades del lenguaje oral conllevan importantes implicaciones para la competencia comunicativa social del niño (Feeney et al, 2016), posibles problemas de conducta y de ajuste psicosocial asociados (Chow & Wehby, 2018;Girard et al, 2016;Yew & O'Kearney, 2015).…”
Section: Discussionunclassified
“…Previous research has identified several challenges with regard to effective collaboration between qualified professionals, for example, reluctance of professionals to give up their role as experts (Baxter et al 2009;Creaghead 1992). In order for collaboration to be successful, there needs to be a willingness to work together and an acceptance by team members of their role of learner as well as specialist (Lacey & Lomas 1993).…”
Section: Fostering Effective Transdisciplinary Collaboration: Undergrmentioning
confidence: 99%